Is It Possible to Reverse the Storage-Induced Lesion of Red Blood Cells? - Barshtein, Gregory; Arbell, Dan; Livshits, Leonid; Gural, Alexander (Frontiers in Physiology, 2018)
Cold-storage of packed red blood cells (PRBCs) in the blood bank is reportedly associated with alteration in a wide range of RBC features, which change cell storage each on its own timescale. Thus, some of the changes take place at an early stage of storage (during the first 7 days), while others occur later. We still do not have a clear understanding what happens to the damaged PRBC following their transfusion. We know that some portion (from a few to 10%) of transfused cells with a high degree of damage are removed from the bloodstream immediately or in the first hour(s) after the transfusion. The remaining cells partially restore their functionality and remain in the recipient’s blood for a longer time. Thus, the ability of transfused cells to recover is a significant factor in PRBC transfusion effectiveness. In the present review, we discuss publications that examined RBC lesions induced by the cold storage, aiming to offer a better understanding of the time frame in which these lesions occur, with particular emphasis on the question of their reversibility. We argue that transfused RBCs are capable (in a matter of a few hours) of restoring their pre-storage levels of ATP and 2,3-DPG, with subsequent restoration of cell functionality, especially of those properties having a more pronounced ATP-dependence. The extent of reversal is inversely proportional to the extent of damage, and some of the changes cannot be reversed.